Design and Research of the Performance of Torque Transmission of Locking Disc used to Wind Turbines - Jing Chaoyin (Jixie chuandong)
The locking disc is the connections between main shaft and input planet stage of wind turbines gearboxs.Because of the high cost of fault maintenance,the requirement of working reliability is more strict.Based on elastic plastic deformation theory of thick wall cylinder in the field of mechanics of materials,and combining the deformation compatibility condition,the calculation method of torque transmission of locking disc is researched,and some important factors which effects the performance of torque transmission are analyzed by combining with practical engineering.It provides theoretical basis for design,manufacturing and improving the working reliability of shrink disc.It is helpful to engineering application.